Pengembangan Media Emoji Berbasis permainan dalam Interaksi Sosial Anak di Kelas - Juniarti, Yenti; Laiya, Sri Wahyuningsi; Sutisna, Icam (UNIVERSITAS SLAMET RIYADI, 2019)
This study aims to facilitate Kiddie Care for Gorontalo children in developing children's social interactions due to the low ability of children to interact both with their peers and the teacher in class. This study uses a research and development approach. While the development model used is the Research & Development (R&D) development model. The results of this study are the social interactions caused by children to their friends when looking for emojis, children feel that this game is emotionally draining because children can express according to the emojis displayed by their friends, then children feel happy when they look for emojis